End-to-End Security Mechanism Using Blockchain for Industrial Internet of Things - Muhammad Shahid, Dildar; Adnan Shahid, Khan; Irshad, Ahmed Abbasi; REEMA SHAHEEN, NASEEM AKHTAR; KHALIL, AL RUQAISHI; SHAKEEL AHMED, GHULAM SARWAR (IEEE, 2025)
The urgent penetration of the Industrial Internet of Things (IIoT) in industrial sectors has fostered unmatched benefits in terms of efficiency, productivity, and overall performance. Although current security frameworks already offer a sound level of protection, they do not adequately scale to the growing diversity and number of devices integrated into the Industrial Internet of Things. They rely on static, centralized network organization and management, which cannot ensure data integrity across a huge number of highly distributed devices. The proposed research provides insight into an innovative end-to-end security solution model, which caters to the needs of IIoT via the introduction of the blockchain. The current security solutions seem to fail in terms of security, scalability, data efficiency, integrity, and the actual needs of IIoT. As a result, the top chance of a cyberattack or similar threat remains high. The proposed work demonstrates that IIoTs may benefit from blockchain frameworks because blockchains reuse existing security mechanisms, enable transaction validation without central trust, and implement appropriate authorization. Additionally, the IIoT environment can benefit from implementing security frameworks that reflect their characteristics. In this paper, an overall solution that employed the decentralized setup of blockchain was proposed for authentication, authorization, and data integrity for all devices. Our approach is free from the need for any central authority. That mechanism is based on smart contracts that enforce security policies. Our framework allows for the switching of any access rule at any time, as well as it can immediately react to some suspicious behavior. In our paper, we proposed some lightweight cryptographic schemes, and Data management overhead which could fit any device. Moreover, our algorithm for the blockchain implementation is hybrid because this approach incorporates all the best features of the private and public implementation due to the individual blocks containing feasible information rather than the entire history.